Therapeutic itinerary of breast cancer women in a border municipality - Andréa Ferrreira Ouchi França; Rosane Meire Munhak da Silva; Aline Aparecida Monroe; Ana Paula Alonso Reis Mairink; Larissa Clara Nunes; Marislei Sanches Panobianco (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to know the therapeutic itinerary and to show the implications of breast cancer for women in a border town in southern Brazil. Methods: a qualitative research conducted based on the complexity paradigm, through interviews with 13 women with breast cancer undergoing outpatient treatment and data analyzed by thematic analysis. Results: the first signs and symptoms of breast cancer were noticed unexpectedly, in everyday moments and during routine visits. There was family support in the search for assistance in primary care services, but organizational barriers led this itinerary to private health services, including Paraguay. Coping with the disease and treatment was anchored in the family subsystem. Final Considerations: the paths for breast cancer diagnosis and treatment included families, primary care services and private health services, including from the neighboring country, considering the vulnerability of border regions to guarantee health care.